AMRI Hospitals:: Impending Challenges for Management of COVID-19 Vaccination, International and Government Funded Insurance Patients - dasgupta, prasanjit (IIUM Journal of Case Studies in Management, 2023)
AMRI Hospitals has three hospitals in Kolkata and one in Bhubaneswar in the eastern part of India. With its 5000 doctors and employees, they serve 450,000 patients annually. The group incurred an operating loss in the first quarter of 2020-21 due to the covid pandemic. The pandemic continued; the subsequent quarterly financial result was not encouraging as they have merely scrapped through operating losses. AMRI Hospitals are feeling challenged: It needs to expedite covid vaccination program to cover the maximum number of people; It needs to decide about continuing with its two centers in Bangladesh since these have become almost non-viable due to restrictions on international travel due to the pandemic; It needs to develop an economic model for treating the patients covered under the state government-funded insurance scheme ’Swasthya Sathi’ as offered rates are not meeting the expenses.